Investigating the Impact of Supply Chain Management on Bank Performance and Bankruptcy prediction using the cumulative density function model (Case Study: Iraqi banks) - Hassan Al-Asadi, Bushra Mohammed Sami; Abdulkareem Zuhaira, Marwah; Kadhum Zwen, Abdulamir Abid (International Journal of Supply Chain Management, 2019)
Abstract Proper supply chain performance plays a crucial role in the success of the banks. Therefore, it is essential to use an appropriate supply chain performance assessment system to continuously improve it. The political and economic developments have played a major role in bringing about changes in the economic environment in general and in the banking environment in particular, in response to these changes or affected by the changes in the banking environment and the successive developments in the financial and banking arena, which expanded the scope of its banking business both internally and internationally. This has been reflected in increased banking risks and thus the possibility of bank defaults resulting in financial and banking instability. The issue of banking failure management has become increasingly important for banks, and has been included by the Basel Committee as an important aspect of determining bank adequacy. As a result of studying and analyzing various aspects related to banking failure. Hence, the importance of this research is highlighted, as it will shed light on the factors and causes of the phenomenon of bankruptcies and identify and address the weaknesses. By adopting the density function, a model for estimating the exposure of banks to the housing. The research came out with a set of conclusions and recommendations